Elaboration and behavior of poly(3-hydroxybutyrate-co-4-hydroxybutyrate)- nano-biocomposites based on montmorillonite or sepiolite nanoclays. (August 2016) - Khandal, Dhriti; Pollet, Eric; Avérous, Luc
Graphical abstract: Highlights: Elaboration and characterization of new nano-biocomposites based on P(3HB- co -4HB). Amazing difference of behavior between sepiolite and montmorillonite-based systems. Great effect of the silanol groups brought by the sepiolite on the final properties. High potential of these nano-biocomposites as renewable & performing materials. Abstract: Poly(3hydroxybutyrate- co -4hydroxybutyrate) (P(3HB- co -4HB)) is a polyhydroxyalkanoate (PHA), which is known for its properties and performance leading to a wide range of applications. Compared to more conventional PHAs such as P(3HB) or P(3HB-4HV), P(3HB- co -4HB) is known for its mechanical properties. P(3HB- co -4HB) has the potential to replace some fossil-based thermoplastics in certain fields. However, it is thermally sensitive like most PHAs and this puts limitations on its potential as an important biobased and biodegradable polymer. The present work is based on the study of multiphase systems of P(3HB- co -4HB) elaborated to prepare nano-biocomposites using two nanoclays, montmorillonite (MMT) and sepiolite (Sep). The clays differ in geometries with MMT having sheet structure and Sep having fiber structure. The environment-friendly non-solvent based elaboration of P(3HB- co -4HB) in the presence of nanoclays allows for minimizing thermal degradation while improving the overall mechanical properties and thermal resistance of the final multiphase materials. The degree of improvement in the properties is found to be not only a function of the clay dispersion in the polymer matrix but also on the morphology/shape of the clay particles and interfacial polymer-clay interactions. It has been found that despite the higher aspect ratio of lamellar-type MMT clays, the fiber-like Sep clay has better stiffening properties arising mainly from the better polymer-clay interactions through the silanol groups along the length of the fiber. As a result of this increased "effective" aspect ratio of Sep, the properties of the Sep-based nano-biocomposites are greatly enhanced. The detailed analyses using various techniques (TGA, DSC, TEM, XRD, uniaxial tensile test) allows comparison and analysis of the structure-property relationships between MMT and Sep nano-biocomposites.